Disclosure and HIV Transmission. (December 2015) - Ryan, Samantha
This paper examines the various approaches to disclosure of HIV infected status identified by the Law Commission in its Scoping Consultation Paper on Reform of Offences against the Person. It argues against the imposition of a general duty to disclose in all circumstances, and further suggests that a requirement for disclosure cannot be justified when there is a low risk of transmission. It suggests that the better approach to disclosure is to be found by combining the remaining two Law Commission proposals. This would mean that whether a person was justified in exposing another to the risk of HIV infection without disclosing their HIV positive status would be a matter for the jury and a key factor relevant to the jury's consideration in this regard would be the level of risk of transmission involved.